From Community Participation to Community Engagement The Call for School Leadership in the Indian Context - Malik, Charu Smita (JOURNAL OF INDIAN EDUCATION, 2018)
Community participation in the Indian education system has largely been operationalised and studied through formal structures, which also forms a part of much of the documented literature. The existence of formal structures based on the community, such as the village education committees, parent-teacher associations, mother-teacher associations, school management development committees, etc., are linked with the larger government policy of decentralisation for encouraging local governance and enabling school-based management. Community participation, through these formal structures, has come to be viewed as synonymous with the functioning or non-functioning of these committees rather than studying the practices of the stakeholders involved, including the school head. While discussing school-community relations in the Indian context, the school as an entity has often subsumed the role of the head of the school and does not explicitly put focus on the behaviour exhibited or practices initiated by them. This paper proposes a shift in the way we perceive community participation and relooks at its key purpose which is to involve the parents and the community with the learning development of the child and be a valuable resource to the school. Drawing from studies on school leadership which study the behaviour and practices of the heads of schools in engineering meaningful community engagement, the paper attempts to position the role of the school head in the framework of School Leadership in the national policy discourse. This re-focus on the agency of the school head as a leader can be useful in bringing the school and community together, keeping the child at the centre.